جهود الشيخ أبي العباس حلولو القروي في خدمة المذهب المالكي - بونور, عبد الحكيم (جامعة الوادي - University of Eloued, 2022)
ملخص: يعد المذهب المالكي من أوسع المذاهب الفقهية انتشارا،وأكثرها أتباعا، و أغزرها إنتاجا، كل ذلك راجع إلى كثرة التلاميذ الذين سمعوا من الإمام مالك، أو من تلاميذه، ثم قاموا بنشر هذه السماعات في بلدانهم و أوطانهم، حتى أصبحت كثير من المناطق مدارس تابعة للمذهب المالكي، خرجت الكثير من الأعلام الذين خدموا المذهب فيما بعد. لذلك كان الهدف من هذه الدراسة بيان جهود الشيخ أبي العباس أحمد حلولو القروي، الذي ولد بزليتن و سمع من علماء القيروان و تونس، ثم أبلى بلاء حسنا في خدمة المذهب،تأليفا و تدريسا و اختيارا، فلا تزال كتبه الأصولية و الفقهية شاهدة عليه إلى اليوم، و هي مليئة باختياراته العلمية، أصولا و فروعا. فالمذهب المالكي انتشر و توسع ولم يندثر، بسبب هذه الجهود و أمثالها، و التي تحتاج إلى دراسة و بيان. Abstract : The Maliki school of thought is one of the most widespread schools of jurisprudence, the most followed, and the most prolific. All of this is due to the large number of students who heard from Imam Malik, or from his students, and then spread these hearings in their countries and countries, until many areas became schools affiliated with the doctrine. Al-Maliki, many of the flags who served the doctrine later emerged. Therefore, the aim of this study was to demonstrate the efforts of Sheikh Abu Al-Abbas Ahmad Halulu Al-Qarawi, who was born in Zliten and heard from the scholars of Kairouan and Tunisia, and then he performed a great deal in the service of the doctrine, writing, teaching and choosing, so his books of fundamentalism and jurisprudence are still witness to him to this day, and It is full of scientific choices, origins and branches. The Maliki school of thought spread and expanded and did not disappear because of these and similar efforts, which need to be studied and explained.
مقال
Keywords: أحمد أبو العباس حلولو الزليتني القروي ; المذهب المالكي ; الجهود المبذولة